The early history of greed : the sin of avarice in early medieval thought and literature - Newhauser, Richard, 1947- (Cambridge studies in medieval literature, 2000)
In this first full study of the early history of greed Richard Newhauser shows that avaritia, the sin of greed for possessions, was increasingly dominant in a wide range of theological and literary texts from the first century CE to the end of the tenth century.